Google images and the youth climate strike 2019 - Jefferson, Joslin (My University, 2020)
On March 15, 2019 students from all over the globe participated in the youth climate strike, a political protest with the goal of getting governments to be more active on the matters of climate change. This study examines multiple aspects of the youth climate strike by means of Google Images using the hashtag #YouthClimateStrike. For this study, a sample of 755 Google Images were collected. We analyzed the source of the image (using hyperlink), the characteristics of protest participants in the images and messaging by using the posters within the image. These variables were analyzed using a hybrid method of qualitative and quantitative analysis. The images were derived from 396 unique websites that posted images from the youth climate strike. Of these photos, 85% contained teenaged individuals, 91% of the images contained legible text, with the top slogan being “there is no planet B” and 58% of the text presented in these images contained demands. Future research will be conducted this summer with a larger sample size to determine how COVID 19 has turned this strike into an online strike. Additionally, new research questions will be explored such as whether the slogans are attacking or blaming the government, or if the images differed by publication sources.
Presented in absentia on April 27, 2020 at "Student Research Day" at MacEwan University in Edmonton, Alberta. (Conference cancelled)